Atonía uterina post parto eutócico simple - Riquero Carvajal, Jeniffer Alexandra (2020)
The postpartum hemorrhage is one of the main causes of obstetrics emergencies. The maternal mortality rate due to hemorrhages ranges from 30% to 50%. The most important risk factors are advanced maternal age and chronic pathologies. It is universally defined as haematic loss above 500 ml following a vaginal delivery or above 1,000 ml following a caesarean. An early postpartum haemorrhage (EPH) is one that occurs during the first 24 hours following delivery and is generally the most serious.The late is what happens after 24 hours after delivery until 6 weeks after it. The causes of PPH include uterine atony, traumas/ lacerations, retention of products of conception and coagulation disorders, the most frequent being atony and the latter can occur due to different factors of which one of them was the factor that triggered the hemorrhage in the present case. Multiparity is associated with an increase in fibrous tissue that can interfere with muscle contraction, since uterine over- distention exhausts the tone of muscle fibers, which is why a multiparous uterus is more prone to atony. It can be prevented by an active mangement of the third stage of labour and its treatment goes from the use of uterotonics drugs to an emergency hysterectomy.